2021
DOI: 10.1080/15548627.2021.1899669
|View full text |Cite
|
Sign up to set email alerts
|

WDR45, one gene associated with multiple neurodevelopmental disorders

Abstract: The WDR45 gene is localized on the X-chromosome and variants in this gene are linked to six different neurodegenerative disorders, i.e., ß-propeller protein associated neurodegeneration, Rett-like syndrome, intellectual disability, and epileptic encephalopathies including developmental and epileptic encephalopathy, early-onset epileptic encephalopathy and West syndrome and potentially also specific malignancies. WDR45/WIPI4 is a WD-repeat β-propeller protein that belongs to the WIPI (WD repeat domain, phosphoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 153 publications
0
10
0
Order By: Relevance
“…Pathways include immune system [83], adaptive immune system [84], neutrophil degranulation [85], cytokine signaling in immune system [86] and GPCR ligand binding [87] were responsible for progression of COVID-19 infection. A previous study demonstrated that the expression levels of AHSP (alpha hemoglobin stabilizing protein) [88], IL7R [89], FBXO7 [90], KLRB1 [91], PIP4K2A [92], NFE2 [93], CCR2 [94], CLEC12A [95], NLRP12 [96], PECAM1 [97], TRIM10 [98], ICAM3 [99], EEF1A1 [100], CCR4 [101], PTPRC (protein tyrosine phosphatase receptor type C) [102], CX3CR1 [103], TSPAN32 [104], EOMES (eomesodermin) [105], ATM (ATM serine/threonine kinase) [106], CD28 [107], LRRK2 [108], CCL5 [109], CD33 [110], FCRL3 [111], CCR3 [112], FGL2 [113], GZMA (granzyme A) [114], PICALM (phosphatidylinositol binding clathrin assembly protein) [115], ALOX5 [116], MME (membrane metalloendopeptidase) [117], VIM (vimentin) [118], CD93 [119], GCA (grancalcin) [120], CD226 [121], CD1D [122], TNFSF4 [123], LEF1 [124], TLR4 [125], CCR7 [126], DPP4 [127], NLRC4 [128], ITGB3 [129], RASGRP1 [130], TLR2 [131], DOCK2 [132], CSF1R [133], PRKCB (protein kinase C beta) [134], CAMK4 [135], CXCL5 [136], CD36 [137], P2RY12 [138], LILRB2 [139], CD5 [140], SLC25A37 [141], ADIPOR1 [142], PECAM1 [143], RGS10 [144], RGS18 [145], ANK1 [146], RNF182 [147], NPRL3 [148], NINJ2 [149], KCNA3 [150], ABCG2 [151], MS4A6A [152], WDR45 [153], RAB39B...…”
Section: Discussionmentioning
confidence: 99%
“…Pathways include immune system [83], adaptive immune system [84], neutrophil degranulation [85], cytokine signaling in immune system [86] and GPCR ligand binding [87] were responsible for progression of COVID-19 infection. A previous study demonstrated that the expression levels of AHSP (alpha hemoglobin stabilizing protein) [88], IL7R [89], FBXO7 [90], KLRB1 [91], PIP4K2A [92], NFE2 [93], CCR2 [94], CLEC12A [95], NLRP12 [96], PECAM1 [97], TRIM10 [98], ICAM3 [99], EEF1A1 [100], CCR4 [101], PTPRC (protein tyrosine phosphatase receptor type C) [102], CX3CR1 [103], TSPAN32 [104], EOMES (eomesodermin) [105], ATM (ATM serine/threonine kinase) [106], CD28 [107], LRRK2 [108], CCL5 [109], CD33 [110], FCRL3 [111], CCR3 [112], FGL2 [113], GZMA (granzyme A) [114], PICALM (phosphatidylinositol binding clathrin assembly protein) [115], ALOX5 [116], MME (membrane metalloendopeptidase) [117], VIM (vimentin) [118], CD93 [119], GCA (grancalcin) [120], CD226 [121], CD1D [122], TNFSF4 [123], LEF1 [124], TLR4 [125], CCR7 [126], DPP4 [127], NLRC4 [128], ITGB3 [129], RASGRP1 [130], TLR2 [131], DOCK2 [132], CSF1R [133], PRKCB (protein kinase C beta) [134], CAMK4 [135], CXCL5 [136], CD36 [137], P2RY12 [138], LILRB2 [139], CD5 [140], SLC25A37 [141], ADIPOR1 [142], PECAM1 [143], RGS10 [144], RGS18 [145], ANK1 [146], RNF182 [147], NPRL3 [148], NINJ2 [149], KCNA3 [150], ABCG2 [151], MS4A6A [152], WDR45 [153], RAB39B...…”
Section: Discussionmentioning
confidence: 99%
“…BPAN (OMIM #300894) manifests as global developmental delay with epilepsy and Rett-like syndrome in childhood and rapid-onset dystonia-parkinsonism and progressive dementia in early adulthood (recently reviewed in [224][225][226]). The WD-domain repeat 45 (WDR45) gene encode a beta-propeller WD repeat protein interacting with phosphoinositides (WIPI4), which is critically involved in the autophagosome-lysosome fusion in neuronal cells [227].…”
Section: Neurodegenerations With Brain Iron Accumulation (Nbia) Groupmentioning
confidence: 99%
“…Another study employing patient-derived fibroblasts found upregulation of DMT1 and downregulation of TfR associated with cellular Fe accumulation induced by nutrient starvation [233]. This pattern of molecular abnormalities led to the hypothesis that mutations in WDR45 may affect ferritinophagy and mitophagy causing deranged Fe recycling with DMT1 upregulation as a proximal cause of Fe accumulation [224]. Impaired ferritinophagy and non-transferrin-bound iron pathway were confirmed to mediate the accumulation of iron in another cellular BPAN model [234] whereby iron was detected mostly in lysosomal vesicles [235].…”
Section: Neurodegenerations With Brain Iron Accumulation (Nbia) Groupmentioning
confidence: 99%
“…The reason for the variety of clinical manifestations associated to WIPI4 mutations (see Cong et al, 2021 for a comprehensive review of the clinical symptoms) is not yet clear and could be due to the influence of genetic and environmental factors.…”
Section: Wipis and Diseasementioning
confidence: 99%